Efektivitas Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Masyarakat di Desa Watu Lanur Kecamatan Lamba Leda Selatan Kabupaten Manggarai Timur - Salma Putri Nurhadi; Khaerul Umam Noer (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
The issue of poverty can be seen as a widespread social phenomenon that impacts various regions and provinces in Indonesia. Poverty can have implications in the fields of health and education. Therefore, various efforts by the government to address poverty-related issues through innovations and policies, one of which is the Program Keluarga Harapan (PKH), are expected to reduce poverty rates in Indonesia. The aim of this research is to understand and analyze the Effectiveness of the Program Keluarga Harapan (PKH) in Enhancing Community Welfare in the Village of Watu Lanur, Lamba Leda Selatan District. This study utilizes a descriptive research method with a qualitative approach, collecting data through interviews, observations, and documentation The identified issues in this study pertain to the amount of assistance received and the perception that the Family Hope Program (PKH) is still not precisely targeted. The research findings indicate that the PKH in the village of Watu Lanur has been able to empower the community, as many people have benefited from the social assistance mandated by government regulations. Based on the effectiveness achieved regarding the implementation of the PKH program in Watu Lanur village, it is evident that the response and efforts of the local government have been commendable, despite some challenges that need to be addressed with solutions.